Population structure of Simmental beef cattle using pedigree analysis - Araujo Neto, Francisco Ribeiro de; Vieira, Dheynne Alves; Abreu Santos, Daniel Jordan de [UNESP]; Pessoa, Matilde Conceicao; Aspilcueta Borquis, Rusbel Raul; Oliveira, Henrique Nunes de [UNESP]; Aarao Marques, Luiz Fernando (Springer, 2020)
The purpose of this study was to estimate parameters related to the population structure and genetic diversity in the Simental breed based on the pedigree information of 77,553 animals. The individual coefficients of inbreeding and average relatedness, number of complete generations, coefficient of change of inbreeding, effective size, effective number of founders, number of ancestors and generation interval were calculated. Using the Simmental cattle information, the mean inbreeding and average relatedness coefficients were 1.49% and 0.99%, respectively. The effective number of founders and ancestors was 163 and 132, respectively, and the effective population size was 48.03. Despite the relatively small inbreeding coefficient, some of the estimated population parameters indicated the need to adopt measures to maintain the genetic variability of the population.
Keywords: Beef cattle; Bos taurus; Breeding program; Genealogy; Genetic variability